Economic and biological characteristics of the new spring oat variety ‘Dzhigit’ - V. A. Boradulina; A. P. Kuzikeeva; G. M. Musalitin; Zh. V. Kuzikeev (Зерновое хозяйство России, 2025)
Throughout the history of oat breeding in Altai, seven varieties have been developed and introduced into the List of Breeding Achievements. Five of them are the varieties ‘Altaiskiy krupnozerny’ (1992), ‘Korifey’ (1999), ‘Pegas’ (2009), ‘Rusich’ (2021), ‘Vektor’ (2021) for grain fodder use, two varieties ‘Argument’ (2005) and ‘Dzhigit’ (2024) are universal. The new oat variety ‘Dzhigit’ was developed by individual selection from the hybrid combination ‘Mutika 551’ x ‘Kalgan’. The crossing was carried out in 2003, the basic plant was selected in 2007. The study in the competitive testing nursery took place in 2013–2024. The State Variety Testing was in 2022, 2023. The current paper has presented the study results of oat varieties in 2022–2024. In the competitive testing nursery, the productivity of the variety ‘Dzhigit’ sown in fallow varied from 4.98 to 6.83 t/ha. The mean productivity was 5.78 t/ha, while the standard variety ‘Vektor’ had 5.12 t/ha with an increase of 0.66 t/ha or 12.9 %. On average, the productivity after the grain forecrop was 3.52 t/ha, which exceeded that of the standard variety by 0.58 t/ha or 19.7 %. Over the years of study, ‘Dzhigit’ has proved to be adapted to unfavorable environmental factors. The advantages of the new variety are as follows: large productivity of grain and green mass, grain size, resistance to lodging and loose smut. The variety ‘Dzhigit’ has been included in the List of breeding achievements approved for use since 2024 in the West Siberian (10), East Siberian (11) regions for grain and mowing purposes, in the Far Eastern (12) for grain purpose.